DERADIKALISASI BERBASIS PEMBERDAYAAN MASYARAKAT MELALUI FORUM KEBANGSAAN KALIMANTAN TIMUR - Akhmad Jubaidi, Mukhamad Ilyasin, dan Hasyim Mi'radje (Prodi Ilmu Administrasi Negara, 2019)
The purpose of this research is to find out and describe the process ofDeradicalization Based on Community Empowerment through the NationalForum on East Kalimantan. This study uses a qualitative approach that takesplace in a reasonable setting using a phenomenological paradigm because itaims to understand the phenomena that occur in research subjects.Participatory action research (participatory action research) isresearch that actively involves all relevant parties (stakeholders) in assessingongoing actions (where their own experience is a problem) in order to makechanges and improvements for the better.In order to stem the spread of Deradicalisation in East Kalimantan,FKPT can make at least three systematic efforts that are expected to have asignificant impact on deterring Deradicalization, namely first strengtheningthe ideology of tolerance in all layers of society in order to foster peacefulbehavior. In this case the role of religious leaders, Customary Leadersbecomes very important as a barometer of community attitudes and mentaldevelopment. Furthermore, the revitalization of values and practice ofPancasila as an ideology of the nation that must be upheld aims to strengthenthe character of citizens and instill a spirit of nationalism in supporting plural,tolerant, and peaceful national life. The last effort is to strengthen the role ofcivil society through FKUB, FKPT, FPK, FKDM, FKPMKT as an extensionof BNPT and government partners who aim to gather massive involvement ofcivil society in the movement to combat Deradicalization and terrorism.